LIVESTOCK FEED SUPPLY IN THE KASHKADARYO REGION (Conferencea, 2024)
This paper explores the agricultural and livestock development in the Kashkadaryo region during the 1920s to 1950s, focusing on the impact of environmental challenges, agricultural reforms, and government policies. It highlights key events such as the 1927 drought, which severely affected livestock, causing widespread livestock deaths due to feed shortages. The study also examines the measures taken to regulate pasture use, including the redistribution of lands from wealthy nomads and the introduction of livestock feeding points. Despite setbacks, such as the failure to meet feed production goals in 1937, the establishment of new pastures between 1945 and 1958 supported livestock growth. However, the area planted with alfalfa decreased over time, especially after 1940, as cotton cultivation expanded. The paper emphasizes the role of Soviet policies in transforming agricultural practices, including crop rotation and the development of irrigated pastures. By the 1960s, despite favorable yields in some years, the livestock sector continued to face challenges due to adverse weather conditions. Ultimately, the research sheds light on the evolving relationship between livestock farming, agricultural practices, and environmental factors in the region.